A method to quantify infection and colonization of holm oak (Quercus ilex) roots by Phytophthora cinnamomi. - Ruiz-Gómez, Francisco J; Sánchez-Cuesta, Rafael; Navarro-cerrillo, Rafael M; Pérez-de-Luque, Alejandro (Plant methods, 2012)
ABSTRACT: Phytophthora cinnamomi Rands. is an important root rot pathogen widely distributed in the north hemisphere, with a large host range. Among others diseases, it is known to be a principal factor in the decline of holm oak and cork oak, the most important tree species in the "dehesa" ecosystem of south-western Spain. Previously, the focus of studies on P. cinnamomi and holm oak have been on molecular tools for identification, functional responses of the host, together with other physiological and morphological host variables. However, a microscopic index to describe the degree of infection and colonization in the plant tissues has not yet been developed. A colonization or infection index would be a useful tool for studies that examine differences between individuals subjected to different treatments or to individuals belonging to different breeding accessions, together with their specific responses to the pathogen. This work presents a methodology based on the capture and digital treatment of microscopic images, using simple and accessible software, together with a range of variables that quantify the infection and colonization process.
Keywords: histology; Holm oak decline; infection degree; Microscopy; Phytophthora; root rot